Effect of task interruption on the situation awareness of air traffic controllers - Zhou, Kun; Wang, Chenglong; Xie, Siqi; Zhou, Yanan; Zhang, Xuelong; Wang, Yanqing; Tang, Hui (PloS one, 2024)
Multiple intersecting situational tasks in the field of aviation often cause air traffic controllers to face issues pertaining to interruption and task switching. To investigate the impact of task interruption on the situation awareness of air traffic controllers, two experiments were conducted. Experiment 1, which focused on 44 new graduates preparing to work in the field of air traffic control, revealed that task interruption reduced the participants’ levels of situation awareness. Experiment 2, which focused on 80 new air traffic control graduates, employed a 2 (primary task modality: visual, auditory) × 2 (interruption modality: visual, auditory) between-subjects design and revealed that the negative effect of task interruption on situation awareness was moderated by task modality. Interruptions that occur in the same modality as the primary task were shown to result in greater decreases than were cross modal interruptions. Visual interruption led to a greater decrease in situation awareness than did auditory interruption, and interruption of the visual task also caused a greater decrease in situation awareness than did interruption of the auditory task. These findings might be valuable in attempts to enhance situation awareness among air traffic controllers by providing insights into the design of human‒computer interactions in the context of an air traffic control automation system.